Effect of Diethylpyrocarbonate on the Antiviral and Interferon-Inducing Activities of Viral and Nonviral Agents - Yamamura, Yasuhiro (1976)
Diethylpyrocarbonate (DEPC) treatment of interferon (IF) inducers was studied both in vitro and in vivo. DEPC did not affect the antiviral activity of poly(I·C), statolon, or reovirus in cultured chicken embryo fibroblast cells, but the activities of poly(I·C), statolon, and MU9 replicative form in cultured mouse embryo cells were markedly reduced by the treatment. Target-organ treatment of Swiss Webster mice with DEPC-treated poly(I·C) produced higher levels of serum IF than did the same procedure with untreated poly(I·C), but the animals were not protected against vaccinial encephalitis. In contrast, DEPC-treated statolon protected the animals, although the peak serum IF level was significantly lower than in those treated with intact statolon. Nevertheless, the antiviral activity of statolon was also found to be mediated by IF, since no activity was seen in Vero cells. DEPC-treated single-stranded ribonucleic acid viruses failed to stimulate IF production, indicating that some viral factor(s) susceptible to DEPC is required for the stimulation observed with untreated viruses.